Integrative analysis of the choroid by quantifying Haller vessel and choriocapillaris parameters in different drusen subtypes - Hyungwoo Lee (Nature Portfolio, 2021)
Abstract This study aimed to quantify the Haller vessel and choriocapillaris (CC) parameters in drusen subtypes in nonexudative age-related macular degeneration (AMD) and pachydrusen. Ninety-five eyes of 80 patients and 28 control eyes were categorized into soft drusen, subretinal drusenoid deposit (SDD), soft drusen plus SDD, pachydrusen, and control groups. The diameter, length and intersections of Haller vessels and the total area, size and number of CC flow voids were quantified using en face optical coherence tomography (OCT) or OCT angiography. The pachydrusen group showed the largest Haller vessel area and diameter and shortest total length but similar CC parameters to those in the control group. The soft drusen plus SDD group showed the largest CC flow void area and size, while the Haller parameters were similar to those in the control group. The area and size of the flow voids in the SDD group were smaller than those in the soft drusen plus SDD group. Based on unsupervised machine learning, the eyes were classified into 4 clusters—the control, pachydrusen, soft drusen plus SDD and soft drusen plus SDD groups. Cluster 3 showed a larger diameter and shorter total length of the Haller vessels than cluster 4.